PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Giswa Ramadhani Wibisono; Handoyo Djoko Waloejo (Jurnal Ilmu Administrasi Bisnis, 2019)
Phenomena of coffee shops has become a rapidly growing business in Indonesia. These business opportunities create a competition between coffee shop companies engaged in providing the best service to attract consumers and retain its consumers. One of the local company that sells coffee drinks is Peacockoffie Gajahmada Semarang. As a company that engaged in service sector, must prioritize a good services to consumers with appropriate price on what has been given by Peacockoffie Gajahmada Semarang. This study aims to determine the effect of service quality and price on purchase decisions (studies on consumers Peacockoffie Gajahmada Semarang). This type of research is explanatory research. The sampling techniques used are incidental sampling and purposive sampling. The number of samples taken is 100 respondents, who are consumers of Peacockoffie Gajahmada Semarang. The research that is used to determine the effect of service quality and price on purchase decisions will present statistics with the help of IBM SPSS version 21.0.